Penguatan Kompetensi Profesional Guru Tersertifikasi Di SD Wilayah Gugus IV Kecamatan Rajadesa Kabupaten Ciamis - Tri Ayu Meilawati (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The background of this research, there are various kinds of problems related to the professional competence of certified teachers. By strengthening professional competence, it is hoped that the competence of certified teachers will increase. The purpose of this study was to analyze and describe: 1) Strengthening the competence of certified teachers in SD Region IV Cluster Rajadesa District, Ciamis Regency; 2) Obstacles faced by certified teachers in strengthening their professional competence in SD Region IV Group, Rajadesa District, Ciamis Regency; 3) Efforts made by certified teachers in strengthening their professional competence in SD Region IV Group, Rajadesa District, Ciamis Regency. The research method used is descriptive with a qualitative approach. Data collection techniques were carried out through interviews, observation, and documentation studies. The informants in this study included school principals and certified teachers. The results of the study show that 1) Strengthening the professional competence of certified teachers in SD Region Gugus IV Rajadesa District, Ciamis Regency in terms of the aspect of professional competence is generally in the criteria of being effective so that it can be said to be good. However, there are aspects that need to be improved, namely the use of technology-based media and learning resources, understanding research in learning and participating in implementing student development; 2) There are obstacles faced by certified teachers in strengthening their professional competence in SD Region IV Group, Rajadesa District, Ciamis Regency; 3) There are efforts made by certified teachers in improving their professional competence in SD Region Cluster IV, Rajadesa District, Ciamis Regency.